Seasonal variation in fitness variables in professional soccer players - Casajus, J. A. (The Journal of Sports Medicine and Physical Fitness, 2001)
BACKGROUND: There have been many studies on soccer, but few evaluations of the physiological function of professional soccer players. The aim of this work was to evaluate seasonal variation - from September to February - in anthropometric and physiological variables in a Spanish professional soccer team (n=15). METHODS: Anthropometric measurements were obtained following the standardised techniques adopted by the International Society for the Advancement of Kinanthropometry (ISAK). A maximal treadmill test with breath-by-breath gas analysis was carried out to evaluate the aerobic condition and a Jump test was used to measure muscle performance and strength in the lower limbs. RESULTS: There were no significant variations in body mass, although a statistically significant decrease (p<0.05) in fat percentage and sum of six skinfolds was observed. The somatotype (Heath-Carter) was mesomorphic without any change observed throughout the season. The mean VO2max in the first test (65.5 ml.kg-1.min-1) had not changed by the second one (66.4 ml.kg-1.min-1). There were no significant differences in maximal heart rate (185 vs 185 beats.min-1) and treadmill speed at VO2max (16.1 vs 15.8 km.h-1). At the anaerobic threshold, there were significant differences (p<0.05) in speed (12.4 vs 13.1 km.h-1) and heart rate (164 vs 168 beats.min-1) as the season progressed. When the data were expressed as a percentage of maximal values obtained, we observed that the speed in the first test was 77 and 83% in the second test. For heart rate, values were 89 and 91%, and for oxygen uptake 77 and 79%. The Jump test did not show any significant change during the season. CONCLUSIONS: We can conclude from these results that professional soccer players have good fitness from the beginning of the Spanish League - with a high VO2max - and the changes observed depend on the initial values. J Sports Med Phys Fitness 2001 Dec;41(4):463-469